Maraviroc Intensification Improves Endothelial Function in Abacavir-Treated Patients, an Open-Label Randomized Cross-Over Pilot Study. Issue 3 (September 2016) - Krikke, Maaike; Tesselaar, Kiki; Arends, Joop; Drylewicz, Julia; Otto, Sigrid; Lelyveld, Steven; Visseren, Frank; Hoepelman, Andy
Abstract Background The increased risk of abacavir in cardiovascular disease (CVD) in HIV-infected patients is still being debated. Maraviroc, a CCR5 blocker, has been shown to decrease immune activation and monocyte infiltration in atherosclerotic plaques in murine experiments. Therefore, we examined the effect of maraviroc intensification on flow-mediated dilatation (FMD) in abacavir-treated HIV-infected patients and its effect on immunological and inflammatory parameters. Methods A open-label prospective crossover study with a duration of 16 weeks: 8 weeks of intervention (maraviroc intensification) and 8 weeks of control (unchanged cART regimen). FMD, HIV-specific variables, expression of HIV co-receptors, markers of inflammation and coagulation and cellular markers of immune activation were measured at weeks 0, 8 and 16. The changes (Δ) in these variables were compared between intervention and control periods using non-parametric tests. To evaluate the relation with the change in FMD, linear regression modeling was used. Results Twenty-one male patients with suppressed plasma HIV-RNA, on cART, had a known HIV infection for 9.2 years (IQR 6.9–13.5) with abacavir use for 6.5 years (2.8–9.3). A significantly increased FMD of 0.73% (IQR −0.25 to 1.70) was seen after maraviroc intensification compared to a decrease of −0.42% (IQR −1.89 to 0.25;p  = 0.049) in the control period. There was a negative relation between ΔFMD with ΔD-dimer (β −22.70, 95% CI −39.27; −6.13, p  = 0.011) and ΔCD95+ CD4+ T cells (β −0.16, 95% CI −0.28; −0.04, p  = 0.013), adjusted for age and duration of HIV. Conclusion Maraviroc intensification modestly improves endothelial function in HIV-infected patients on an abacavir-containing regimen. Trial registration NCT01389063.